Effectiveness and Safety of Twice- Versus Thrice-Daily Subcutaneous Heparin for Venous Thromboembolism Prophylaxis at a Large Academic Medical Center. Issue 5 (May 2022) - Wiethorn, Eryne E.; Harrison, Sarah; Weeda, Erin R.; Bell, Carolyn Magee
Background: Dosing variation of subcutaneous unfractionated heparin (UFH) exist for venous thromboembolism prophylaxis (VTEP). Objective: The purpose of this study was to compare the safety and effectiveness of thrice-daily (TID) versus twice-daily (BID) administration of UFH during a heparin shortage for VTEP. Methods: A single-center retrospective analysis was conducted in patients with orders for BID subcutaneous UFH during a heparin shortage from September 1, 2019, to February 4, 2020. These patients were matched to patients with TID subcutaneous UFH orders from January 1, 2019, to May 31, 2019. The primary outcome was the incidence of deep-vein thrombosis or pulmonary embolism confirmed by imaging during hospitalization. The secondary outcome was the incidence of major or clinically relevant nonmajor bleeding events as defined by International Society on Thrombosis and Haemostasis (ISTH) definitions. Results: A total of 277 patients with orders for BID UFH and meeting inclusion criteria were evaluated and matched to patients who received TID UFH. After the exclusion criteria were implemented, 510 patients remained in the TID group. The primary outcome occurred in 4% of patients in the BID group and 3% in the TID group ( P = 0.645). Major bleeding or clinically relevant nonmajor bleeding events occurred in 10% of patients in the BID group and 8% in the TID group ( P = 0.310). Conclusion and Relevance: There was no difference in effectiveness or safety of TID versus BID subcutaneous UFH for VTEP. During a heparin shortage, transitioning patients to BID UFH for VTEP to conserve supply may be considered.